Rural students' transition in and through a semi-urban university: Experiences from the National University of Lesotho - Pulane Lefoka; Tebello Tlali (University of Johannesburg, 2021)
This paper reports on the findings of a study carried out at the National University of Lesotho (NUL). The paper explored the influence of 'rurality' on students who originate from the rural areas of Lesotho and analysed their transition at the NUL. The spatial geographic theory and narrative inquiry were adopted, and qualitative focus groups were utilised to collect data. The students were given an opportunity to conceptualise 'rurality' and narrate their stories about growing up and earlier schooling, as well as their learning experiences at the NUL. The findings revealed that rural students' educational trajectories are indeed filled with numerous challenges, mainly due to deprivation and limited exposure to technology in their earlier lives. The main recommendation made by the paper is that the concerned stakeholders ought to be mindful of the needs of all prospective higher education students, including those from rural backgrounds, and intervene accordingly.